Antarctic Rahnella inusitata : A Producer of Cold-Stable β-Galactosidase Enzymes - Kattia Núñez-Montero; Rodrigo Salazar; Andrés Santos; Olman Gómez-Espinoza; Scandar Farah; Claudia Troncoso; Catalina Hoffmann; Damaris Melivilu; Felipe Scott; Leticia Barrientos Díaz (International Journal of Molecular Sciences, 2021)
There has been a recent increase in the exploration of cold-active β-galactosidases, as it offers new alternatives for the dairy industry, mainly in response to the current needs of lactose-intolerant consumers. Since extremophilic microbial compounds might have unique physical and chemical properties, this research aimed to study the capacity of Antarctic bacterial strains to produce cold-active β-galactosidases. A screening revealed 81 out of 304 strains with β-galactosidase activity. The strain Se8.10.12 showed the highest enzymatic activity. Morphological, biochemical, and molecular characterization based on whole-genome sequencing confirmed it as the first Rahnella inusitata isolate from the Antarctic, which retained 41–62% of its β-galactosidase activity in the cold (4 °C–15 °C). Three β-galactosidases genes were found in the R. inusitata genome, which belong to the glycoside hydrolase families GH2 (LacZ and EbgA) and GH42 (BglY). Based on molecular docking, some of these enzymes exhibited higher lactose predicted affinity than the commercial control enzyme from Aspergillus oryzae . Hence, this work reports a new Rahnella inusitata strain from the Antarctic continent as a prominent cold-active β-galactosidase producer.